2016
DOI: 10.18632/aging.100980
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed HDAC4 is associated with poor survival and promotes tumor progression in esophageal carcinoma

Abstract: Histone deacetylases (HDACs) mediate histone deacetylation, leading to transcriptional repression, which is involved in many diseases, including age-related tissue degeneration, heart failure and cancer. In this study, we were aimed to investigate the expression, clinical significance and biological function of HDAC4 in esophageal carcinoma (EC). We found that HDAC4 mRNA and protein are overexpressed in esophageal squamous cell carcinoma (ESCC) tissues and cell lines. HDAC4 overexpression is associated with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 39 publications
7
75
0
Order By: Relevance
“…Disruption of the HDAC4-RelB-p52 complex by a HDAC4-mimetic polypeptide blocks the growth of multiple myeloma (16). Zeng et al (17) demonstrated that HDAC4 was overexpressed in esophageal squamous cell carcinoma, and HDAC4 overexpression was associated with an advanced clinical stage and poor survival. HDAC4 inhibition sensitized lung cancer A549 cells to doxorubicin resistance by reducing the phosphorylation of signal transducers and activators of transcription-1 (STAT1) and the expression of epidermal growth factor receptor (EGFR), which suggested an interaction between HDAC4, STAT1 and EGFR (18).…”
Section: Histone Deacetylase Hdac4 Promotes the Proliferation And Invmentioning
confidence: 99%
“…Disruption of the HDAC4-RelB-p52 complex by a HDAC4-mimetic polypeptide blocks the growth of multiple myeloma (16). Zeng et al (17) demonstrated that HDAC4 was overexpressed in esophageal squamous cell carcinoma, and HDAC4 overexpression was associated with an advanced clinical stage and poor survival. HDAC4 inhibition sensitized lung cancer A549 cells to doxorubicin resistance by reducing the phosphorylation of signal transducers and activators of transcription-1 (STAT1) and the expression of epidermal growth factor receptor (EGFR), which suggested an interaction between HDAC4, STAT1 and EGFR (18).…”
Section: Histone Deacetylase Hdac4 Promotes the Proliferation And Invmentioning
confidence: 99%
“…Histone deacetylase 4 (HDAC4) plays global roles in the regulation of gene transcription, cell growth, survival and proliferation, and their aberrant expressions or activities contribute to cancer development . Zeng LS revealed that upregulated HDAC4 is associated with higher tumor grade, advanced clinical stage, and poor survival rate in esophageal carcinoma, also they found that HDAC4 promoted proliferation and G1/S cell cycle progression in EC cells . Vallabhapurapu SD demonstrated that HDAC4 and its downstream complex maintained repressive chromatin around pro‐apoptotic genes Bim and BMF and regulates multiple myeloma (MM) survival and growth .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Zeng LS revealed that upregulated HDAC4 is associated with higher tumor grade, advanced clinical stage, and poor survival rate in esophageal carcinoma, also they found that HDAC4 promoted proliferation and G1/S cell cycle progression in EC cells. 11 Vallabhapurapu | 4585 SUN aNd QIN SD demonstrated that HDAC4 and its downstream complex maintained repressive chromatin around pro-apoptotic genes Bim and BMF and regulates multiple myeloma (MM) survival and growth. 12 Marroncelli N reported that HDAC4 regulated satellite cell proliferation and differentiation by targeting P21 and Sharp1 genes.…”
Section: Introductionmentioning
confidence: 99%
“…This can likely be explained by the inability of the TNM staging system to accurately predict the prognosis of patients with resectable ESCC [7]. Some patients with early-stage ESCC rapidly develop local and regional recurrences and distant metastases after esophagectomy [8]. Therefore, it is imperative to identify novel prognostic biomarkers to assist oncologists in improving the predictive accuracy of the TNM staging system for ESCC.…”
Section: Introductionmentioning
confidence: 99%